Лиловая книга сказок. Любимые детские сказки - Пыльцына Елена Евгеньевна (Радуга сказок, 2005)
Экземпляры: ф.2 (2006) / Инвентарный номер: 49825 / Цена: / Сис.шифр: 82.3(0)-6 / Авт.знак: Л 57 / ГРНТИ: 17.71.91 / ББК: 82.3(0)-6